The speech of the Owner in the letters of love of César Moro - Pacheco Quispe, Jhonny Jhoset (2019)
He studies a cartography of three themes that underlie César Moro’s poetry, specifically the Equestrian Turtle (1957) and Letters to Antonio (1938-1939). In the first, the “metaphor of Love” is analyzed in which the gestation of love is established, and the loving lyrical speech of a loved one, Erómenos, towards a lover, erastés. In the second, the concept of the “Discourse of the Master”, which shows a hierarchy and subordination of power between the actuators, the master and the Slave, which generates various implications inserted as a axis of poetic functioning; From this, it is mentioned the idea of a great literary letter that wanted to make the author of Amour à mort, as can be collected and inferred in texts written during the Mexican period (1938-1948). Finally, it analyzes the Letters to Antonio, on topics such as the camouflage with the reality, the mythical thought, the destruction of the referent, etc.